THE POSITION OF HEIRS FROM INTERFAITH MARRIAGES IN THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 71/PUU- XX/2022 AND CIVIL INHERITANCE - Hanafi Urwatil Usqo; Arifuddin Muda Harahap; Ramadhan Syahmedi Siregar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this study is to determine the position of heirs from interfaith marriages in the analysis of the decision of the constitutional court number 71/PUU- XX/2022, Interfaith marriages often cause problems in terms of legal status and inheritance rights, especially in Indonesia which has cultural and religious diversity. This research uses a normative juridical approach with the aim of examining various legal phenomena through analysis of the relationship between legal norms and their impact. The data used as the basis for this research is secondary data, which consists of various sources such as books, scientific journals, and academic articles. The results of the research indicate. Based on Constitutional Court Decision No. 71/PUU-XX/2022, it confirms that interfaith marriages that are not valid according to religious law cannot be recognised by the state. The state asserts that the validity of a marriage depends on the provisions of religious law, not just administrative registration. Because the petition was formally rejected (because it did not fulfil the legal standing requirements), the Court did not assess the substance of the norm being tested, so there was no change to the legal position of interfaith marriages. The provisions of Constitutional Court Decision No. 71/PUU-XX/2022 have not provided adequate constitutional protection for heirs of interfaith marriages. The rejection of the petition on formal grounds resulted in no change to the norm in Article 2 paragraph (1) of the Marriage Law.